ESTIMASI PENERIMAAN PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN LOMBOK UTARA - Baiq Kisnawati; Irianto Irianto (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
This study aims to estimate receipts revenue (PAD) in North Lombok regency. By estimating local authorities have an idea of the extent of his ability to run the regional autonomy in the future. This type of research is classified as descriptive research. Variables to be researched the development of revenue (PAD) using data periodically from 2009 to 2015. Analysis of the data regarding our reception area while using the descriptive analysis to estimate the acceptance of PAD using analytical tools Trend Linear Least Squares Method (Method of Least Square). The results showed that the income of acceptance Realization (PAD) in 2009 up to 2015, an average of 59.9% comes from local tax revenue, 13.5% of the levies, 1.9% Income results Wealth Management Areas separated and 24.7% of the other legal PAD. Realization of local revenues derived from PAD 10.47%, 87.70% came from revenue transfer, and 1.83% comes from other legitimate income areas. Thus it can be said that the contribution of revenue from PAD to total local revenues in North Lombok is very little that is 10.47%. This indicates that the level of Financial dependencies North Lombok regency government against the central government is very high, especially from Central Government Transfers - Balance Fund. The average growth in revenue during the year of observation in 2009 to 2015 is still low in terms of quantity as well as with the average estimate of PAD acceptance for the future that is 2016 and 2020 are also low in terms of quantity despite estimated revenue estimation PAD terms the percentage will be increased by an average 20% per annum or at Rp 328,983,938,234.31 year